CTP Synthase 1 Is a Novel Therapeutic Target in Lymphoma. Issue 4 (28th April 2023) - Asnagli, Hélène; Minet, Norbert; Pfeiffer, Christina; Hoeben, Eef; Lane, Rebecca; Laughton, David; Birch, Louise; Jones, Geraint; Novak, Andrew; Parker, Andrew E.; Ludwig, Heinz; Fischer, Alain; et al.
Abstract : Lymphoma is the most common hematological malignancy and is among the 10 most prevalent cancers worldwide. Although survival has been improved by modern immunochemotherapeutic regimens, there remains a significant need for novel targeted agents to treat both B-cell and T-cell malignancies. Cytidine triphosphate synthase 1 (CTPS1), which catalyzes the rate-limiting step in pyrimidine synthesis, plays an essential and nonredundant role in B-cell and T-cell proliferation but is complemented by the homologous CTPS2 isoform outside the hemopoietic system. This report describes the identification and characterization of CTPS1 as a novel target in B- and T-cell cancers. A series of small molecules have been developed which show potent and highly selective inhibition of CTPS1. Site-directed mutagenesis studies identified the adenosine triphosphate pocket of CTPS1 as the binding site for this small molecule series. In preclinical studies, a potent and highly selective small molecule inhibitor of CTPS1 blocked the in vitro proliferation of human neoplastic cells, showing the highest potency against lymphoid neoplasms. Importantly, pharmacological CTPS1 inhibition induced cell death by apoptosis in the majority of lymphoid cell lines tested, thus demonstrating a cytotoxic mechanism of action. Selective CTPS1 inhibition also inhibited the growth of neoplastic human B- and T- cells in vivo. These findings identify CTPS1 as a novel therapeutic target in lymphoid malignancy. A compound from this series is in phase 1/2 clinical studies for the treatment of relapsed/refractory B- and T-cell lymphoma (NCT05463263). Abstract :